Financial Contribution of Iranian Urban Households in the Health System (2004-2016): With an Emphasis on the Health Transformation Plan - Ali Akbar Fazaeli (Journal of Education and Community Health)
Background and Objectives: One of the most important objectives of the health transformation plan (HTP) is to reduce out-of-pocket payment of households for healthcare services. In this study, we investigated the financial participation of Iranian urban households in the health sector before and after the development plan. Materials and Methods: In this cross-sectional retrospective study, we investigated healthcare payments of households considering their economic characteristics and using household budget survey in urban areas of Iran during 2004-2016. Descriptive statistics were used in Excel 2016 to analyze the data. Results: Household health expenditures amounted to 11857892 IRR in 2012, with a significant growth of 16021227 IRR in 2013 and a slower growth to 19031440 IRR in 2014. In higher income deciles, health expenditure had a greater role in household expenditures, such that more than 6.3% of the expenditures of the 10th income decile were devoted to healthcare, while in the first decile it was less than 4.8%. Conclusion: Growth of health care expenditures in 2014 was lower than in 2013. Although other factors, including decreasing inflation rate, have been effective in reducing the growth rate of household health costs, the HTP can be implicated in this change, as well.